ADVANCING AN AUTOMATED EVALUATION IN THE DESIGN OF A CURTAIN WALL - Almerino, Porferio M (Journal of Agriculture and Technology Management; Vol 25 No 1 (2022): Vol 25 No 1 (2022): Journal of Agriculture and Technology Management (JATM) Volume 25 January - June 2022 Issue, 2024)
Proprietors are generally conscious as to the cost implication of a project. This impels the industry to resourcefully seek ways and means to at least satisfy both owners and what the American Architectural Manufacturers Association (AAMA) standards have, in particular, spelled out as regards aluminum curtain wall (CW). In Cebu, Philippines, the prevailing approach in assessing the design of CW is through manual computation. However, experiences in the field saw likelihood for this method to trigger calculation deficiency or error during the technical appraisal. To mitigate probable risks in the computational process, the present study advances an automated evaluation that timely, conveniently and safely assesses a CW design and departs from the traditional way. Findings showed that a shift from manual computation using the identified formulas of mathematical science to an automated evaluation can indeed boost a swift, easier, and safer design of curtain wall. However, further investigation on such technological acceptance and utilization specifically among the small-scale players is recommended.